2018
DOI: 10.21037/apm.2017.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Supportive & palliative interventions in motor neurone disease: what we know from current literature?

Abstract: Although there is no cure for motor neurone disease (MND), the advent of supportive interventions including multidisciplinary care (MDC) has improved treatment interventions and enhanced quality of life (QOL) for MND patients and their carers. Our integrative review showed evidence-based MDC, respiratory management and disease-modifying therapy that have improved the outcomes of patients diagnosed with MND. Supportive approaches to nutritional maintenance and optimization of symptomatic treatments, including m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…127 The MDT approach is also important to ensure that all the patient’s concerns are addressed, including the needs of their family and primary caregivers. 128…”
Section: Models Of Carementioning
confidence: 99%
“…127 The MDT approach is also important to ensure that all the patient’s concerns are addressed, including the needs of their family and primary caregivers. 128…”
Section: Models Of Carementioning
confidence: 99%
“…They found that major factors related to IMV avoidance were female gender, NIV use longer than 6 months, bulbar onset, and absence of spouse/partner [139]. It is also important to consider that these patients get used to NIV, and over time they become dependent on it, so it becomes difficult to opt for IMV [140]. Moreover, ALS patients during NIV show a decreased pain threshold leading to avoidance of further invasive procedures, increased social restrictions, and raised psychological barriers against transition from NIV to IMV [141].…”
Section: Ethical Dilemmasmentioning
confidence: 99%
“…The burden of becoming dependent on NIV is very distressful and it sums up to the other discouraging experiences that this fatal disease carries with itself [138, 140, 148]. Withdrawing from long-term NIV has not fully been explored.…”
Section: Ethical Dilemmasmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is a fatal disease, with degeneration of upper and lower motor neurons and a high burden of symptoms not unlike that of cancer 1 . Supportive interventions including multidisciplinary care and optimization of symptom treatments have improved quality of life for these patients and palliative care remains the cornerstone of ALS management 2‐10 …”
Section: Introductionmentioning
confidence: 99%